Back Cover: Discovery of a Single Monooxygenase that Catalyzes Carbamate Formation and Ring Contraction in the Biosynthesis of the Legonmycins (Angew. Chem. Int. Ed. 43/2015). Issue 43 (17th July 2015) - Huang, Sheng; Tabudravu, Jioji; Elsayed, Somayah S.; Travert, Jeanne; Peace, Doe; Tong, Ming Him; Kyeremeh, Kwaku; Kelly, Sharon M.; Trembleau, Laurent; Ebel, Rainer; Jaspars, Marcel; Yu, Yi; et al.
<x xml:space="preserve">Abstract</x> The multifunctional Baeyer–Villiger enzyme LgnC catalyzes the transformation of indolizidines into pyrrolizidines by carbamate formation, hydrolysis, decarboxylation‐driven ring contraction, and hydroxylation. In their Communication on page 12697 ff., H. Deng, Y. Yu et al. show that these are the crucial steps for the biosynthesis of the legonmycins, new bacterial pyrrolizidine alkaloids named after their association with Legon, Ghana.